Determination of The Amount of Levy and Profit Sharing for Parking Management based on The Regulation of The Mayor of Surakarta No.5 of 2024 - Gresnia Himbi Parkitasari; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
The increase in motorized vehicles in Surakarta demands more effective and efficient parking management. The Surakarta City Government stipulates Mayor Regulation No. 5 of 2024 as the basis for regulating parking levies to increase Regional Original Revenue (PAD) and ensure regular parking management. This study aims to analyze the suitability of the amount of parking levy in Surakarta Mayor Regulation No. 5 of 2024 with higher laws and regulations and examine the implementation of these regulations in parking management practices in Surakarta, including the obstacles faced. This study uses a normative method with a legislative approach to assess the suitability of parking levy rules against higher regulations and an empirical method to evaluate policy implementation in the field. The study shows that the amount of the parking levy in Surakarta Mayor Regulation No. 5 of 2024 is not fully aligned with higher regulations, especially in terms of tariff adjustments based on people's purchasing power and the principle of fiscal justice. In addition, the implementation of this regulation faces various obstacles, such as a lack of socialization with parking attendants, uneven parking facilities, and the emergence of illegal collection practices. Therefore, it is necessary to revise policies and increase supervision so the parking levy system can run more optimally.